Can We Predict Usage of Dental Services? An Analysis from Germany 2000 to 2015. (October 2020) - Schwendicke, F.; Krois, J.; Jordan, R.
Objectives: We aimed to predict the usage of dental services in Germany from 2000 to 2015 based on epidemiologic and demographic data, and to compare these predictions against claims within the statutory health insurance. Methods: Indicators for operative (number of coronally decayed or filled teeth, root surface caries lesions, and fillings), prosthetic (number of missing teeth), and periodontal treatment needs (number of teeth with probing pocket depths (PPDs) ≥ 4 mm) from nationally representative German Oral Health Studies (1997, 2005, 2014) were cross-sectionally interpolated across age and time, and combined with year- and age-specific population estimates. These, as well as the number of children eligible for individual preventive services (aged 6 to 17 y), were adjusted for age- and time-specific insurance status and services' utilization to yield predicted usage of operative, prosthetic, periodontal, and preventive services. Cumulative annual usage in these 4 services groups were compared against aggregations of a total of 24 claims positions from the statutory German health insurance. Results: Morbidity, utilization, and demography were highly dynamic across age groups and over time. Despite improvements of individual oral health, predicted usage of dental services did not decrease over time, but increased mainly due to usage shifts from younger (shrinking) to older (growing) age groups. Predicted usage of operative services increased between 2000 and 2015 (from 52 million to 56 million, +7.8%); predictions largely agreed with claimed services (root mean square error [RMSE] 1.9 million services, error range −4.6/+3.8%). Prosthetic services increased (from 2.4 million to 2.6 million, +11.9%), with near perfect agreement to claimed data [RMSE 0.1 million services, error range −8.3/+3.9%]). Periodontal services also increased (from 21 million to 27 million, +25.9%; RMSE 5.2 million services, error range +21.9/+36.5%), as did preventive services (from 22 million to 27 million, +20.4%; RMSE 3 million, error range −13.7/−4.7%). Conclusion: Predicting dental services seems viable when accounting for the joint dynamics of morbidity, utilization, and demographics. Knowledge Transfer Statement: Based on epidemiologic and demographic data, predicting usage of certain dental services is viable when accounting for the dynamics of morbidity, utilization, and demographics.